Does timing of endoscopy affect outcomes in patients with upper gastrointestinal bleeding: a systematic review and meta-analysis. Issue 8 (August 2021) - Aziz, Muhammad; Dasari, Chandra Shekhar; Zafar, Yousaf; Fatima, Rawish; Haghbin, Hossein; Alyousif, Zakaria Abdullah; Lee-Smith, Wade; Perisetti, Abhilash; Nawras, Ali; Garg, Shashank; Inamdar, Sumant; Tharian, Benjamin
Abstract : Background and aims: The timing of esophagogastroduodenoscopy (EGD) for the management of upper gastrointestinal bleeding (UGIB) remains controversial. Early EGD (E-EGD) (within 24 h of presentation) has been compared to late EGD (L-EGD) (after 24 h) in numerous studies with conflicting results. The previous systematic review included three randomized controlled trials (RCTs); however, the cutoff time for performing EGD was arbitrary. We performed an updated systematic review and meta-analysis of the studies comparing the outcomes of E-EGD and L-EGD group. Methods: A comprehensive search of PubMed, EMBASE, Cochrane Library, and Web of Science was undertaken to include both RCTs and cohort studies. Primary outcomes including overall mortality and secondary outcomes (recurrent bleeding, need for transfusion, and length of stay) were compared. Risk ratios and standardized mean difference (SMD) with 95% confidence interval (CI) were calculated. Results: A total of 13 observational studies (with over 1.8 million patients) were included in the final analysis. No significant difference in overall mortality (risk ratio: 0.97; CI, 0.74–1.27), recurrent bleeding (risk ratio: 1.12; CI, 0.62–2.00), and length of stay (SMD: –0.07, CI, –0.31 to 0.18) was observed for E-EGD group compared to L-EGD group. The possibility of endoscopic intervention was higher in E-EGD group (risk ratio: 1.70, CI, 1.28–2.27). Consistent results were obtained for subgroup analysis of studies with 100% nonvariceal bleed (NVB) patient (risk ratio: 1.12; CI, 0.84–1.50). Conclusion: Given the outcomes and limitations, our meta-analysis did not demonstrate clear benefit of performing EGD within 24 h of presentation for UGIB (particularly NVB). Abstract : Supplemental Digital Content is available in the text.